Characteristics of Dutch ED patients and their journey through the acute care chain: A province-wide flash-mob study - Lieke Claassen; Patricia Maria Stassen; Thimo Jozef Theresia Boumans; Dennis Gerard Barten; Marjolein Nel Tinie Kremers; Anne Maria Elisa Hermans; Noortje Zelis; Jochen Wilco Lennert Cals; Gideon Hubertus Petrus Latten (PLoS ONE, 2025)
Background Insight in characteristics and journey of patients in the Acute Care Chain (ACC) who visit the Emergency Department (ED) is lacking. Existing studies focus on prespecified (time-sensitive) complex conditions like major trauma and stroke, and on the hospital phase. This study provides a representative overview of adult ED patients and their journey through the ACC with focus on differences between those with and without prespecified complex conditions. Methods A prospective 72-hour flash-mob study was conducted in 2022 across all six EDs in the province of Limburg, the Netherlands, encompassing unselected adult patients. Baseline characteristics, journey, and time within ACC were collected. Patients with a prespecified complex condition (stroke, myocardial infarction, aortic syndrome and major trauma) were compared to those without. Results Out of 794 adult ED patients, 585 (73.7%) were included. Patients reported symptoms for a median of 1 day (IQR 0-4) before their ED visit; 56.3% encountered ≥ 1 healthcare provider. General practitioners referred 56.1% of patients, and emergency medical services transported 32.9%. The median time in ACC was 5.0 hours (IQR 3.5-6.9), with 3.0 hours (IQR 2.0-4.2) spent in the ED. The three most prevalent presenting complaints were minor trauma (28.5%), abdominal pain (14.6%) and dyspnoea (12.5%), while 9.3% presented with prespecified complex conditions. Patients with a prespecified complex condition were more often triaged highly urgent (53.6% vs 13.9%, p < 0.001) and received a complex work-up (79.6% vs 41.2%, p < 0.001). Conclusion In our province-wide study, ED patients had symptoms for 1 day and over half of them already contacted a healthcare provider. Time in ACC was 5 hours, with a substantial proportion of time spent prehospitally. Prespecified complex conditions accounted for less than 1 in 10 ED patients. These findings highlight that, to optimise care and care policy, it is essential to examine the entire ACC for unselected patients. Trial registration ClinicalTrials.gov NCT06079099